2022
DOI: 10.1002/jcaf.22548
|View full text |Cite
|
Sign up to set email alerts
|

Audit quality, corporate governance, firm characteristics and CSR disclosures—Evidence from Indonesia

Abstract: The purpose of this study is to investigate the impact of Big 4 auditors, corporate governance and firm characteristics on CSR disclosure in large listed firms in Indonesia adopting the stakeholder theory. The financial and corporate governance data are collected via the Indonesian Stock Exchange for the top 80 firms from 2016 to 2020 while data for CSR disclosures are hand collected from the annual report/sustainability report using the latest Global Reporting Initiative (GRI) 2020 index based on the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…In Nigeria, Abba and Sadah (2020) highlighted that AQ is higher when the auditors understand the industry well enough, and in turn this will give more credibility to the stakeholders, hence increasing the FV. Additionally, CSR disclosure and the FV can have a more significant impact when the relationship is linked to AQ, according to Handayati et al. (2022), when the audit is performed with high quality this will have a positive impact on the FV.…”
Section: Data Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…In Nigeria, Abba and Sadah (2020) highlighted that AQ is higher when the auditors understand the industry well enough, and in turn this will give more credibility to the stakeholders, hence increasing the FV. Additionally, CSR disclosure and the FV can have a more significant impact when the relationship is linked to AQ, according to Handayati et al. (2022), when the audit is performed with high quality this will have a positive impact on the FV.…”
Section: Data Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…The Big Four firms are widespread providers of CSR assurance. As such, they can encourage companies to voluntarily disclose CSR information and devise various marketing and sales strategies to ensure the disclosure of sustainability reports (Dakhli, 2022;Gomes, Eugénio, & Branco, 2015;Handayati et al, 2022;Jahid, Yaya, Pratolo, & Pribadi, 2023).…”
Section: Degree Of Internationalization and Csrmentioning
confidence: 99%
“…For instance, Ong and Djajadikerta (2018) found significant positive correlations between the extent of sustainability disclosures and the proportion of independent directors, multiple directorships and female directors on the board. Handayati et al (2022) found that diligent boards and firms audited by Big 4 auditors have a positive and statistically significant relationship with CSR disclosure. However, the role of corruption has been overlooked in prior research.…”
Section: Theoretical Considerationsmentioning
confidence: 99%